The Effect of Information Technology Utilization and Internal Control on Regional Financial Information Systems and Their Impact on The Quality of The Financial Statements of The Riau Islands Provincial Government - Wahyu Saputra, Okta; Fitri Anggraeni, Annisa; Roswinna, Winna (Dinasti Information and Technology, 2024)
Several things that influence agency performance are the use of information technology and internal control. Information technology and physical internal control are two different things, but IT can be used as a tool to make it easier to carry out internal control and that does not mean that without IT internal control cannot be carried out, it can still be carried out, it's just that with IT it will be much easier because there are things - things that are difficult to achieve by manual internal control. The aim of this research is to examine the influence of the use of information technology and internal control on the regional financial information system and its impact on the quality of the Riau Islands Provincial Government's financial reports. The aim of the research is to determine the use of information technology within the Riau Islands Provincial Government. To find out internal control within the Riau Islands Provincial Government. To find out about the information system in the Riau Islands Provincial Government. To determine the quality of financial reports in the Riau Islands Provincial Government. To determine the influence of the use of technology and internal control on regional financial information systems. To determine the influence of regional financial information systems on the quality of financial reports. The research method is quantitative. Data analysis is an activity after data from all respondents has been collected. Data processing is carried out by means of data that has been collected, processed and presented in tabular form to facilitate the author's processing in preparing this thesis using classified secondary data to facilitate analysis using SEM-PLS. Based on the results of the research conducted, it can be concluded that the use of ICT has a positive and significant effect on the quality of regional financial reports. Internal Control has a positive and significant effect on the Quality of Regional Financial Reports. The Regional Financial Information System has a positive and significant effect on the Quality of Regional Financial Reports. The use of ICT has a positive and significant effect by moderating the Regional Financial System on the Quality of Regional Financial Reports. Internal Control has a positive and significant effect by moderating the Regional Financial Information System on the Quality of Regional Financial Reports.